Some New Records of Marine Gastropod from the Iraqi Coast - Yasser, A. Gh.; Naser, M. D.; Abdul-sahib, I. M. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2022)
Eight marine gastropod records were recorded from the north west of the ArabianGulf, Iraqi coast during March 2020. Th e species are Turritella cochlea Reeve, 1849 (family Turritellidae),Rhinoclavis fasciata (Bruguière, 1792) (family Cerithiidae), Semiricinula tissoti (Petit de la Saussaye,1852) (family Muricidae), Ancilla castanea (G. B. Sowerby I, 1830) (family Ancillariidae), Bulla ampullaLinnaeus, 1758 (family Bullidae), Oliva bulbosa (Röding, 1798) (family Olividae), Naria turdus (Lamarck,1810) and Erronea caurica quinquefasciata (Röding, 1798) (family Cypraeidae). Th ese records raise thenumber of marine gastropods from the Iraqi coast to 40 species.